Avoiding hazardous prescribing. Issue 8 (August 2013) - Avery, Tony; Gookey, Gill; Spencer, Rachel; Knox, Richard; Marsden, Kate; Salema, Ndeshi
Around one in 13 of the prescribing errors detected in the General Medical Council-funded PRACtICe study involved either contraindications or hazardous drug-drug combinations In this article we focus on these issues and also cover the problem of selecting the wrong drug, or drug strength, from computer-based drop-down menus. The article gives the reader opportunities to reflect upon different scenarios involving hazardous prescribing, and there are also suggestions for additional continuing professional development activities.